Evaluation of the Mechanization Level of Aldeia Nova Farm - Albino, Mário Alfredo; de la Rosa-Andino, Alain Ariel; do Souza Neto, Fernando; Isaac Spinola, Manuel Octávio; Morales Tamayo, Yoandrys (Revista Ciencias Técnicas Agropecuarias, 2023)
Agricultural mechanization plays a major role in food production. Its proper implementation requires knowing the indicators that affect its performance. The aim of the present investigation was to evaluate the main mechanization indices of Aldeia Nova Farm in Cela Municipalty. For this, the execution of the study consisted of a non-experimental descriptive investigation, which was divided into two parts. The first consisted of collecting personal data for the operation of the machine and tractor park, maintenance and repair, as well as production. Subsequentle, the mechanization indicators were determined by following methodological recommendations established by various authors. Within the results, the ratio values of tractors per hectare (0,008 tract ha-1), the ratio of average power per tractor (108,86 kW tract-1), the machines per tractor ratio (2,05), the ratio of arable hectares per tractor (126,5 ha tract-1) and the ratio of arable hectares per combine (631,25 ha col-1) were magnitudes studied that behaved outside the established. Finally, the level of mechanization of Aldeia Nova Farm was evaluated using the indices established for this purpose, and it was shown that it is low, since although the value of the available power per hectare (0,86 kW ha-1) is higher than the 0,75 kW ha-1 established in the specialized literature, the rest of the indicators register unfavorable magnitudes, except technical assistance indicators.